The influence of using social network on publishing and serving islam: A case study of jordanian students - Nassar I.A.; Hayajneh J.A.; Almsafir M.K. (IEEE Computer Society, 2023)
Social network one of the most used communication media between people. Nowadays, many researches on the effect of use social network in teaching and learning, some concentrate on Islamic impacts on students. This study, focus on the effects of social network on serving, and publishing Islam. In this study, the main purposes included studies in which field students benefit from social network, making the Islamic information accessible over the world for Muslims, and non-Muslims, also to clarify the Islamic issues, wrong thoughts, and misunderstanding of non-Muslims about Islam. This was measured using survey spread over 500 students focusing on social network usage, purposes, Islamic effects. Participations were chosen from different student education types: schools, undergraduate, and graduate students. The results indicate that, students use more than one social network such as: Facebook, Twitter, Linkedln, Hi5, etc. The students almost use Facebook 97%. Students discuss different type of questions while using social network Islamic topics discussed by 40%, different Islamic topics discussed, and different Islamic sites introduced for members. The response of being a religious man as a member is very low, members thing it is very important for them to be one of the member a religious man. According to the results, Islamic information increased by 78%. This means that the social network is highly used as a way to serve and publish Islam. On the other hand, religion, and Da'wah men must concentrate to be effective members on social networking to get better results in publishing, and serving Islam. 2012 IEEE.